OPPORTUNITIES AND CHALLENGES BENTENG PANCASILA CAMPUS AT SEBELAS MARET UNIVERSITY - Sutimin, Leo Agung; Bramastia; Djono; Winarno; Rawanoko, Endrise Septina; Tarsidi, Deni Zein; Salsalova, Andrea (PRODI PENDIDIKAN PANCASILA DAN KEWARGANEGARAAN STKIP PGRI SUMENEP, 2025)
Sebelas Maret University Surakarta declared itself a Pancasila Fortress Campus, one of its objectives being to prevent the recurrence of events that undermined the Pancasila ideology in the past, including radicalism and intolerance; this was announced when UNS commemorated Pancasila Day on 1 October 2018. As a consequence of this declaration, UNS has constructed six places of worship located in a single area, namely: Mosques, Catholic churches, Christian churches, Buddhist temples, Hindu temples, and Chinese temples. This study uses qualitative methods, with data collection techniques using document studies or documentation, namely from books and articles related to the challenges of Pancasila as the ideology and foundation of the Republic of Indonesia. In efforts to strengthen itself as a Pancasila Fortress Campus, there are several programs and activities that have been and continue to be implemented, including Pancasila Education lectures; Citizenship Education; and the establishment of the Pancasila Implementation Study Centre (PSPP). The challenges faced by UNS as a Pancasila Fortress Campus include individualism, market liberalism, radicalism, religious fundamentalism; the weakening of the practice and actualisation of Pancasila; and the lack of Pancasila role models.